Teachers, Parents and Educationalists' Perceptions towards Introducing English at Early Stage in Libyan Schools: An Explanatory Study - Mohammed Ramadan (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
This study has sought to explore the teachers, parents, and educationalists' understudy perceptions towards the introduction of English language at an early stage in Libyan schools and their possible reasons for supporting/opposing this idea. For this purpose the study employed a quantitative research design with a close- ended questionnaire in order to obtain the essential data for the study. Data was then analyzed manually and the main findings indicated that the study's participants generally agree with the idea of introducing English at an early stage because they believe that teaching English at such stage can a) make pupils very proficient in English, b) develop pupils' cognitive abilities, c) lead pupils to a better academic performance in their education; d) increase pupils motivation for learning in the future. On the other hand, those who opposed introducing English did so because they thought it may a) negatively influence the pupils’ acquisition of their mother language, Arabic; b) increase the burden on pupils; c) invade pupils’ native culture. Keywords: perception, early stage, introducing English, Libyan schools